Evaluation of Social Protection Performance in EU Countries: Multiple-criteria Decision Analysis (MCDA) - Marković, Milan; Stanković, Jelena J.; Digkoglou, Panagiota; Marjanović, Ivana (Problemy Ekorozwoju, 2022)
The paper aims to rank European Union (EU) countries according to the composite index, which uses selected social protection indicators from the relevant database at EU level – Eurostat. The total score of social performance for 2020 was determined using the CRITIC-TOPSIS framework. The study showed that Austria, Luxembourg and Germany, respectively, had the best level of social protection, while Latvia, Romania and Spain were at the bottom, as the countries with the worst values of indicators. The importance of research is reflected in the fact that the social component of sustainable development is still not sufficiently researched, especially when it comes to the application of multi-criteria analysis methods in the empirical analysis of social sustainability. In this regard, depending on the obtained performance values, socio-economic policymakers can redesign existing measures and programs, as well as the amounts of social transfers to certain EU member states. The authors expect that the results of the study will help build higher social standards and well-being in the EU.